Comparison of NO2 diffusion tube measurement methods and related uncertainties - David Medland; Gabriel Garcia; Tom Gardiner; Nicholas A. Martin; Valerio Ferracci; Ashley Wilkins; David Fryer; Tom Holmes; Pete Edwards; Sebastian Diez; David Butterfield (Atmospheric Environment, 2025)

Monitoring of indoor air quality at a large sailing cruise ship to assess ventilation performance and disease transmission risk - Ho Yin Wickson Cheung; Prashant Kumar; Sarkawt Hama; Ana Paula Mendes Emygdio; Yingyue Wei; Lemonia Anagnostopoulos; John Ewer; Valerio Ferracci; Edwin R. Galea; Angus Grandison; Christos Hadjichristodoulou; Fuchen Jia; et al. (Science of The Total Environment, 2025)

Revisiting the Concentration Observations and Source Apportionment of Atmospheric Ammonia - Yuepeng Pan; Mengna Gu; Yuexin He; Dianming Wu; Chunyan Liu; Linlin Song; Shili Tian; Xuemei Lü; Yang Sun; Tao Song; Wendell W. Walters; Xuejun Liu; et al. (Advances in Atmospheric Sciences, 2020)

Modelling the effect of the 2018 summer heatwave and drought on isoprene emissions in a UK woodland - Frederick Otu‐Larbi; Conor G. Bolas; Valerio Ferracci; Zosia Staniaszek; Roderic L. Jones; Yadvinder Malhi; Neil R. P. Harris; Oliver Wild; Kirsti Ashworth (Global Change Biology, 2020)
Projected future climatic extremes such as heatwaves and droughts are expected to have major impacts on emissions and concentrations of biogenic volatile organic compounds (bVOCs) with potential implications for air quality, climate and human health. While the effects of changing temperature and photosynthetically active radiation (PAR) on the synthesis and emission of isoprene, the most abundant of these bVOCs, are well known, the role of other environmental factors such as soil moisture stress are not fully understood and are therefore poorly represented in land surface models. As part of the Wytham Isoprene iDirac Oak Tree Measurements campaign, continuous measurements of isoprene mixing ratio were made throughout the summer of 2018 in Wytham Woods, a mixed deciduous woodland in southern England. During this time, the United Kingdom experienced a prolonged heatwave and drought, and isoprene mixing ratios were observed to increase by more than 400% at Wytham Woods under these conditions. We applied the state‐of‐the‐art FORest Canopy‐Atmosphere Transfer canopy exchange model to investigate the processes leading to these elevated concentrations. We found that although current isoprene emissions algorithms reproduced observed mixing ratios in the canopy before and after the heatwave, the model underestimated observations by ~40% during the heatwave–drought period implying that models may substantially underestimate the release of isoprene to the atmosphere in future cases of mild or moderate drought. Stress‐induced emissions of isoprene based on leaf temperature and soil water content (SWC) were incorporated into current emissions algorithms leading to significant improvements in model output. A combination of SWC, leaf temperature and rewetting emission bursts provided the best model‐measurement fit with a 50% improvement compared to the baseline model. Our results highlight the need for more long‐term ecosystem‐scale observations to enable improved model representation of atmosphere–biosphere interactions in a changing global climate.